2021
DOI: 10.1039/d1md00120e
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically stable apelin-analogues, incorporating cyclohexylalanine and homoarginine, as potent apelin receptor activators

Abstract: Cyclohexylalanine- and homoarginine-substituted apelin analogues are demonstrated to be metabolically stable APJR agonistic peptides with hypotensive effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…It was reported that apelin-13 can decrease blood pressure (BP) and increase heart rate (HR) [ 28 , 29 , 30 , 31 , 32 , 33 ] ( Figure 2 ).…”
Section: Cardiovascular Effects Of Apelinsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that apelin-13 can decrease blood pressure (BP) and increase heart rate (HR) [ 28 , 29 , 30 , 31 , 32 , 33 ] ( Figure 2 ).…”
Section: Cardiovascular Effects Of Apelinsmentioning
confidence: 99%
“…Therefore, the long-term cardioprotective effect of a chronic daily single administration of elabela-32, apelin-13, and Pyr1-apelin-13 in animals with MI or pressure overload is surprising [ 55 , 58 , 60 , 62 , 66 ]. The duration of the hypotensive effect of apelin-13 and apelin-17 analogues to remain stable during enzymatic hydrolysis before reducing BP in mice was about 60 min [ 33 ]. It is quite obvious that apelins that remain stable during enzymatic hydrolysis with a long half-life have the greatest prospects for clinical use in the treatment of stroke, acute myocardial infarction, and in the prevention of adverse myocardial remodeling.…”
Section: The Synthetic Analogues Of Apelinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The system is a suitable pharmacological target: recent discoveries of novel synthetic Apelin-receptor ligands with increased half/life (LIT01-196, l-homoarginine aks l-hArg, and non-canonical amino acids l-cyclohexylalanine aka l-Cha, etc.) and antagonists have paved the way towards clinical trials [ 8 , 9 , 10 ]. For a comprehensive review of the newly synthesized APLNR ligands, refer to Fischer et al [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Vederas’ group has worked on modifications of the NEP cleavage site. They obtained agonists with good affinity and stability, but without studying the potential for signaling bias . In addition, many efforts have been made in recent years to develop small molecule agonists of the APJ receptor. , Nevertheless, the development of peptide analogues allows an easy and rapid approach for structure–activity relationship (SAR) studies and functional selectivity, which is still poorly understood.…”
mentioning
confidence: 99%